THE ROLE OF HYPERBARIC OXYGEN THERAPY IN FOURNIER'S GANGRENE: LITERATURE REVIEW - Vincenza Giordano; Luca Cardillo (OPI Napoli, 2021)
Introduction: Fournier's Gangrene is a severe necrotising infection that can be fatal if not recognised and treated immediately. Treatment consists of a combination of conventional therapy with a multidisciplinary approach (early diagnosis, surgical debridement, antibiotic therapy, intensive care and reconstructive surgery) and adjuvant therapy with hyperbaric oxygen therapy sessions. Objective: To identify the role and evaluate the efficacy of hyperbaric oxygen therapy in Fournier's gangrene. Method: To conduct the following narrative review a research question was outlined using the PIO methodology. Subsequently, a literature review was conducted using the PubMed, Scopus and CINAHL Complete databases from December 2020 to February 2021. Results: Eight studies emerged from the literature review showing that the use of adjuvant Hyperbaric oxygen therapy (HBOT) in combination with classical treatment has beneficial effects and enhances the efficacy of hyperbaric oxygen therapy, resulting in lower mortality rates, in contrast to the average number of hospital days spent in intensive care, which do not undergo any significant change. But in contrast to mortality, the average number of days spent in intensive care differed significantly in favour of the standard treatment group. Conclusion: The combined effect of hyperbaric oxygen therapy with conventional therapy offers a significant advantage in the management of FG; furthermore, HBOT is associated with a significant survival advantage.